Market entry and foreign direct investment - Frank Stähler (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2004)
This paper discusses the impact of foreign direct investment (FDI) on market entry and welfare in a model of two countries and two periods. In the first period, firms enter the market as national firms, in the second period, FDI is possible. The paper demonstrates that FDI reduces market entry because equilibrium profits in the second period decline with a decrease in the fixed cost of FDI. Therefore, compared to a trade regime without any FDI, prices rise in the first period but decline in the second period. The paper shows, however, that FDI will unambiguously improve the sum of discounted consumer surplus.
Keywords: F12; F15; 330; Foreign direct investment; multinational enterprises; imperfect competition; free entry